A Neuropsychological Intervention Study of Intellectual Activity in an Adolescent with Autism Spectrum Disorder - Lenia E. Meza-Salcido; Omar E. Torrado-Duarte; Yulia Solovieva (Национальный психологический журнал)
Background. Autism Spectrum Disorder (ASD) is characterised by difficulties in social communication and restrictive, repetitive patterns of behaviour. ASD represents a spectrum of functional manifestations, involving varying levels of severity in intellectual activity and social interaction. Adolescence involves various physical and cognitive changes, as well as increased social demands. The historical-cultural neuropsychology framework provides an effective theoretical and methodological approach to establish the level of functional development of brain mechanisms and allows for the description of the individual manifestation of the disorder. Objective. This study aims to describe the neuropsychological evaluation and intervention process from a historical-cultural perspective in a case of ASD during adolescence. Study Participants. A 12-year-old, male student with delays in language acquisition and socialisation, as well as psychomotor challenges. These difficulties led to a diagnosis of Global Developmental Delay, ASD, and Attention Deficit Disorder by a child psychiatrist. Methods. A neuropsychological intervention programme was implemented based on the principles of the historical-cultural approach. The programme specifically focused on the development of the affective-emotional sphere, in particular socio-affective communication, and on improving the understanding of oral and written information. Results. Among the results obtained, there was an improvement in expressive and receptive language, with an increase in the use of gestures, facial expressions, and eye contact, fostering more effective communication. The adolescent also demonstrated a greater understanding of social and emotional situations, as well as progress in understanding abstract concepts and problem-solving. Conclusions. The results obtained support the efficacy of neuropsychological interventions based on the historical-cultural perspective to improve the quality of life for individuals with ASD.